Effect of supplementation with organic acids on productive and reproductive parameters in guinea pigs - Vela, Christian; Morales-Cauti, Siever (Revista de Ciencias Agrícolas, 2020)
Guinea pig production systems demand organic alternatives to improve their productivity, due to the increased demands of this type of livestock operations. The present study aimed to evaluate the effect of organic acids on the productive and reproductive indices in reproductive Guinea pigs in an intensive breeding farm in Lima. 60 pools were used with 10 Guinea pigs in each one (9 females and one male). They were randomly divided into 4 treatment groups: T1: 1mL/L, T2: 2mL/L, T3: 4mL/L; all with 15 pools in total (5 pools each with dosage of 5, 10 and 15 days, respectively), and T4: Control (15 pools without dosage); the observation period was 3 months. No significant difference was found (p> 0.05) between treatments for weight gain, percentage of maternal mortality, percentage of abortions, percentage of pregnancy, number of offspring born and percentage of viability. For the percentage of mortality of pups and average weight of the offspring, a significant difference was found (p <0.05), demonstrating that T3 reached a higher weight index at birth of offspring (T3: 147.7 / 142.7 / 146.8g) and lower percentage of mortality in rabbits (T3: 0 / 1.8 / 3.0%). No significant difference was found in terms of dosing days. It is concluded that supplementation with organic acids with T3 (4mL/L) improved the weight at birth of the offspring and the mortality percentage in kits.